Efektivitas Minyak Atsiri Serai Wangi (Combypogon nardus) Sebagai Insektisida Alami Untuk Kecoa Amerika (Periplaneta americana) - Anindita Riesti Retno Arimurti (Universitas Muhammadiyah Surabaya, 2017)
ABSTRAK Cockroaches are one of the most common types of insects around our neighborhood, and it is one of the most dangerous insects because some species of cockroaches are known to transmit disease in humans such as tuberculosis, typhoid, asthma, cholera, and hepatitis. Eradication of cockroaches can be done physically and chemically, the use of chemical-based insecticides can cause respiratory problems. In an insecticide drug containing natural ingredients contain essential oils, the content of essential oil compounds serve as an anti-insect drug on citronella. This study aimed to determine the effect of essential oils of citronella fragrance to cockroaches. This type of research was experimental. The population in this study were cockroaches (Periplaneta americana) obtained from the houses of villagers of Tanjung, Sampang, Madura. The total sample was 32 adult stage cockroaches. Data analysis was using free T test with error rate of 5% or 0,05.The results showed that cockroaches stopped moving with an average of 15.75. Based on T test results showed the significant results of 0.00 which was smaller than 0.05 then H0 was rejected Ha was accepted. It can be concluded that the essential oils of citronella fragrance have an effect on the death of cockroaches. Keywords: Cockroach, Essential Oil Of Citronella Fragrance (Cymbopogon nardus)